Demand Discipline of Air Transportation for Passengers - Yunqian Qu; Jinfu Zhu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The Yangtze River Delta (YRD) region in China is taken for an example to research demand discipline of air transportation for passengers in this paper. The discipline includes three parts: demand generation, distribution and flow. First of all, the key factors influencing demand generation are got with information entropy. A threshold is set to choose more important factors and weights of these factors are calculated at the same time. Contribution rate of a factor is definedto analyze the difference of the factors for different city. By comparing demand distribution with airports’ throughput, we can analyze the demand flow. There are some conclusions. The factors have different contribution rate to different city for demand generation. Aircraft movement is the most important factor influencing demand flow. It provides more accurate basis for market positioning and developing, airport layout in a multi-airport system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2499